STRATEGI GURU DALAM PENYAMPAIAN PEMBELAJARAN DI MASA PANDEMI COVID-19 DI SD N 005 KECAMATAN SENAPELAN - Delisa Asma; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study examines the teacher’s strategy in delivering learning during the Covid-19 pandemic at SD N 005 Senapelan sub-distric, the Covid-19 pandemic in 2020 in Indonesia, this has an impact on various institutions, educational institutions in particular, whose face-to-face learning system must change to an online learning system as ordered by the government for mutual safety in order to reduce the chain of spread of the Covid-19 outbreak. Everything is done from home, including elementary schools, having to learn from home using various existing technology systems, this is a challenge for a teacher who has to find a way to convey material to students as usual. Data were collected through interviews, observations, and documents. Data analysis is descriptive qualitative, the research subjects needed from this research are classroom teachers and parents of first, third, and sicth grade students. The results of the study show that classroom teachers at SD N 005 Kecamatan Senapelan sub-district convey learning when the online system uses mobile phones, and uses WhatsApp, zoom, goole meet, xrecorder applications, each teacher has a different strategy or method of delivering and using learning applications. Evaluate each sub-theme and see students’ understanding through the assignments given. Keywords : Seacher Strategy, Online Learning, Evaluation